Upaya Peningkatan Kerjasama Siswa Melalui Permainan Kaulianan Barudak - Yusup, Ujang Maulana (CV. ITTC INDONESIA, 2024)
This article aims to analyze the collaborative character education that occurs in Kaulinan Barudak Overtime. Kaulinan Barudak is a game that has the value of cooperation to improve the quality of implementing character education. A concept of the character of cooperation is able to increase the ability to interact, the confidence of students and Kaulinan Barudak is actually not just a game just for fun, but this activity is part of Ethno Pedagogic and character education which contains the seeds of discipline lessons, self-confidence, living together, social sensitivity, even the most important thing is the content of cultural morals. The issues that will be discussed in this article regarding the implementation of character education in enhancing cooperation through Kaulinan Barudak Overtime. It is hoped that the implementation of collaborative character education in Kaulinan Barudak Overtime students can have self-confidence, be polite, care for the environment, and be honest in every behavior and action.